Rural development : learning from China - Aziz, Sartaj (London : Macmillan Press, 1978)
This book speaks to two current interests with respect to agricultural development. First is the interest in understanding more fully the consequences of economic development in many countries, particularly less developed countries. While performance as measured by aggregate criteria seems to be relatively impressive and average incomes increasing, it is now clear that more than a decade of rapid growth in less developed countries has been of little or no benefit to a large portion of the rural population. Secondly, since China has devised a unique strategy for rural development that might offer lessons for other countries, interest in analysing the China experience has rise The book tries to provide an understanding on the effect of the ideological impulse, compares quite critically with the often hopeless situation in other developing countries, and is not reluctant to accuse First World countries.
Includes index.
Includes bibliographical references: p. 190-193.
lje 24/01/2018
Keywords: Rural development